A rare cause of gastric outlet obstruction - Suna, Nurettin; Öcal, Serkan; Özer Etik, Diğdem; Selçuk, Haldun; Hilmioğlu, Fatih; Boyacıoğlu, Sedat (Turkish Journal of Gastroenterology, 2017)
Abstract Cite this article as: Suna N, Öcal S, Etik DÖ, Selçuk H, Hilmioğlu F, Boyacıoğlu S. A rare cause of gastric outlet obstruction. Turk J Gastroenterol 2017; 28: 419-20.